Neglect in Childhood, Problem Behavior in Adulthood - Dubowitz, Howard (Journal of interpersonal violence, 2022)
Few studies have reported problem behaviors in adulthood related to the timing of child neglect. The objective was to examine the relationship between classes of child neglect and later behavior. The sample included 473 participants from the prospective Longitudinal Studies of Child Abuse and Neglect (LONGSCAN); their mean age was 23.8 years. They completed an online survey regarding behaviors and experiences in early adulthood. Neglect was assessed via Child Protective Services (CPS) and self-reports of neglect. Latent class analysis (LCA) identified three classes: Late Neglect, Chronic Neglect, and Limited Neglect. There were significant differences between Limited and Late Neglect regarding later intimate partner aggression and violence (IPAV) and psychological distress, and among all classes for criminal behavior. High-risk youth experiencing neglect beginning in mid-adolescence appear especially vulnerable to later criminal behavior, psychological distress, and IPAV. Those working with such youth can help ensure that their needs are adequately met, to prevent or mitigate problems in adulthood.